Coordinated demand-controlled ventilation strategy for energy-efficient operation in multi-zone cleanroom air-conditioning systems. (15th March 2021) - Zhuang, Chaoqun; Shan, Kui; Wang, Shengwei
Abstract: Cleanrooms can be 10–100 times as energy-intensive as typical office buildings. The causes of this are mainly high air change rates and counteraction (i.e. overcooling and reheating) processes in applications. Existing studies have addressed the design and control of outdoor and supply air ventilation systems separately without considering the interaction between them, which causes significant energy waste. This study therefore proposes a coordinated demand-controlled ventilation (CDCV) strategy to achieve energy-efficient operation in multi-zone cleanroom air-conditioning systems, by coordinating operation between outdoor and supply ventilation systems. The Lorenz curve and Gini index are introduced to quantify the demand diversity of multiple zones, and degrees of overcooling and overdrying are used to quantify the mismatch between cooling supply and demand. Cleanrooms in a pharmaceutical factory located in Hong Kong, a humid sub-tropical city, are selected to test and validate the effectiveness of the proposed strategy. Test results show that the optimization of supply air volume can alleviate the mismatch between cooling supply and demand, as well as affect the optimal outdoor air ventilation mode. The proposed strategy can achieve up to 89.6% of reheating and 63.3% of overall energy savings. Highlights: A novel "coordinated demand-controlled ventilation strategy" is proposed for cleanrooms. Lorenz curve and Gini index are used to quantify demand diversity of multiple zones. Mismatch between cooling supply and demand is alleviated by optimizing supply air volume. Up to 89.6% reheating and 63.3% overall energy savings can be achieved.